1998
DOI: 10.1107/s0909049597016877
|View full text |Cite
|
Sign up to set email alerts
|

Angle-resolved UV photoelectron spectra (UPS) of thin films of perylene-3,4,9,10-tetracarboxylic dianhydride on MoS2

Abstract: Angle-resolved UV photoelectron spectra (ARUPS) were measured for thin ®lms of perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) deposited on cleaved MoS 2 surfaces. The take-off angle ( ) dependence of the photoelectron intensity of the highest % band showed a sharp maximum at = 32±34 . A spectral feature of the binding energy at $8.9 eV, which is believed to originate from a % state, showed a remarkably different dependence from that of the % band. A quantitative analysis of the observed dependencies cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…In general, when large -conjugated planner molecules, such as PTCDA and phthalocyanines lie flat on the substrate surface, the dependence of the photoelectron intensity from the single band, which spreads over the molecule, showed a value of max ϭ32°-36°with very sharp angular distribution due to the initial-state interference effects. 5,7,10 The broader angular distribution for the X band suggests that the molecular plane becomes tilted by the reaction after In deposition.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In general, when large -conjugated planner molecules, such as PTCDA and phthalocyanines lie flat on the substrate surface, the dependence of the photoelectron intensity from the single band, which spreads over the molecule, showed a value of max ϭ32°-36°with very sharp angular distribution due to the initial-state interference effects. 5,7,10 The broader angular distribution for the X band suggests that the molecular plane becomes tilted by the reaction after In deposition.…”
Section: Resultsmentioning
confidence: 97%
“…We have already reported that the dependence of the top -band intensity of PTCDA thin films grown on MoS 2 surfaces showed little film-thickness dependence for the film thickness of 1.4-42 Å and the molecules lie with molecular plane being parallel ͑molecular tilt angle of ␤ϭ0°͒ to the substrate surface. 7 The angular dependence of the band X intensity shows a maximum at max ϭ36°-40°with a broader angular distribution than the top band of the pristine PTCDA. In general, when large -conjugated planner molecules, such as PTCDA and phthalocyanines lie flat on the substrate surface, the dependence of the photoelectron intensity from the single band, which spreads over the molecule, showed a value of max ϭ32°-36°with very sharp angular distribution due to the initial-state interference effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that several publications address the adsorption of PTCDA on Ag [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] or other surfaces [2,[19][20][21][22][23][24][25], and also similar molecules have been investigated as adsorbates [1,2,7,20,[26][27][28][29][30][31][32][33]. Here, we concentrate on the chemical bonding and on electronic interface states using several complementary high-resolution techniques.…”
Section: Introductionmentioning
confidence: 97%